2009
DOI: 10.1021/cg8001674
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of the Influence of Divalent Cationic Dopants on the Bulk and Surface Properties of Ba(NO3)2 Associated with Crystallization

Abstract: The incorporation of divalent cationic species associated with the crystallization of Ba(NO 3 ) 2 related to nuclear waste storage issues is studied via the development and exploitation of a versatile and transferable empirical atom-atom forcefield for both mono-and divalent nitrates. Studies of binary and tertiary systems using Mott-Littleton and bulk supercell defect calculations reveals Ca 2+ ions to be the most energetically favored species for incorporation into the Ba(NO 3 ) 2 lattice over Sr 2+ and Pb 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
(46 reference statements)
0
9
0
Order By: Relevance
“…From the results, it can be found that the observed induction times follow the Poisson distribution throughout the experiment time frame, giving a good fit (R 2 > 0.98) to the logarithmic form of eqn (2)(3)(4)(5)(6). The increased rate of primary nucleation was graphically observed from the slope of the distributions and quantified as a drop in the mean induction time.…”
Section: Crystallization Kineticsmentioning
confidence: 74%
See 1 more Smart Citation
“…From the results, it can be found that the observed induction times follow the Poisson distribution throughout the experiment time frame, giving a good fit (R 2 > 0.98) to the logarithmic form of eqn (2)(3)(4)(5)(6). The increased rate of primary nucleation was graphically observed from the slope of the distributions and quantified as a drop in the mean induction time.…”
Section: Crystallization Kineticsmentioning
confidence: 74%
“…[1][2][3] Crystal habits not only play an important role in downstream operations such as product separation, packaging, transportation and storage, but also affect the product's quality and solubility, thus influencing the API's bioavailability and efficiency. 2,4,5 A systematic study on the crystal habits of APIs can guide the optimization of the crystallization process, further improving the properties of the products. 6,7 Conventionally, the selection of suitable solvents and additives is the main route of crystal regulation.…”
Section: Introductionmentioning
confidence: 99%
“…experimental lattice dynamics. All previous force-fields show instabilities in the phonon spectra for at least some of the alkali nitrate polymorphs to which they were fitted except for those of Hammond [5]. This indicates that the structures obtained using previous force-fields were calculated using the full crystal symmetry and will distort away from the experimental crystal space group if the symmetry constraint is reduced or removed.…”
Section: Resultsmentioning
confidence: 99%
“…Several previous force-fields have been developed (e.g. Hammond et al [5] (Li, Rb), Ribeiro et al [6] (Li, Na, K, Cs), Xie et al [7] (Li, Na, K), Ni et al [8] (Li, Na, K), Mort et al [9] (Na, K) and Jayaraman et al [10] (Li, Na, K)). These have been developed for high temperature molten mixtures (Ribeiro, Jayaraman), solutions (Hammond, Xie, Ni), and defect chemistry (Mort) but no force-field has been developed that can be used across all of the alkali metal nitrates and none of them are really suitable for investigating crystallisation.…”
Section: Introductionmentioning
confidence: 99%
“…These crystals were revealed to possess many merits for SRS process, including larger Raman gain coefficient, stable thermal and mechanical properties, good chemical stability, non-deliquescence, and small volume etc. However, the relatively low anti-optical damage threshold and the long cut-off wavelength restricted their applications for SRS in the ultraviolet waveband [16,17].…”
Section: Introductionmentioning
confidence: 99%